Integrated Hydrological and Hydraulic Modeling for River Freezing Simulation: Impacts of a Changing Climate on the Freeze-Up of the Exploits River in Newfoundland - Ghoreishi, Mohammad; Lindenschmidt, Karl-Erich; Barrette, Paul; Khan, Amir Ali (Environmental Modeling & Assessment, 2024)
This version of the article has been accepted for publication, after peer review (when applicable) and is subject to Springer Nature’s AM terms of use, but is not the Version of Record and does not reflect post-acceptance improvements, or any corrections. The Version of Record is available online at: https://doi.org/10.1007/s10666-024-10006-w NRC’s Climate Resilient Built Environment Initiative (1–426543-1323–8000) Peer Reviewed Frazil ice, a major component of winter river dynamics, poses hazards through ice jam formation, particularly in regions like Newfoundland, Canada. This study employs an integrated hydrological and river ice hydraulic modeling approach to predict future freeze-up ice jamming events in the Exploits River under climate change scenarios. Focusing on the naturally flowing lower subbasin, the study simulates streamflow and frazil ice generation by integrating HEC-HMS and RIVICE models. Climate scenarios from the Coupled Model Intercomparison Project (CMIP) phase 6 are incorporated using the delta change method. This study aims to evaluate the generation and accumulation of frazil ice and predict future trends in freeze-up ice jamming events. Our study reveals significant insights into the future dynamics of ice cover extents along the Exploits River, particularly in relation to the town of Badger. Notably, our findings indicate a trend toward shorter ice cover durations and later arrivals of the ice cover front at Badger, potentially mitigating flood risk, particularly during milder winter seasons. Moreover, in some scenarios, the projected ice cover may not even reach Badger during these milder winters, further reducing the town’s vulnerability to flooding events. This research is crucial for ensuring infrastructure resilience and community safety in regions where frazil ice dynamics play a critical role in riverine hazards.